Design research and geotechnologies in high school level under the view of transdisciplinarity (Research, Society and Development, 2020)
In this article, we present a didactic-pedagogical intervention that was developed as a transdisciplinary instrument in the search for redirection of teaching-learning processes through the exploration of geotechnologies used as theoretical and conceptual support for the apprehension and appropriation of school knowledge. From this perspective, this work contemplates the investigation and presentation of a didactic sequence (SD) elaborated according to the principles of design research and the implementation of spatial thinking in basic education: a way of thinking associated with the development of competences for understanding and appropriation of knowledge of the geographical space interrelating aspects inherent to society and the environment. In our construction, the curriculum contents of the Common National Curriculum Base (BNCC) were analyzed and associated with the use of geoprocessing software as didactic-pedagogical resources. The result was an SD systematized by the combination of technology, innovation and dynamism as resources for stimulating and developing the application capacity of emerging technologies. Thus, we propose a reflection on the current teaching methodologies through the presentation of a transversal knowledge approach with access to several areas of knowledge.